The Presence of Uveitis Is Associated with a Sustained Response to the Interleukin (IL)-1 Inhibitors Anakinra and Canakinumab in Behçet's Disease. (17th February 2020) - Fabiani, Claudia; Vitale, Antonio; Rigante, Donato; Emmi, Giacomo; Lopalco, Giuseppe; Di Scala, Gerardo; Sota, Jurgen; Orlando, Ida; Franceschini, Rossella; Frediani, Bruno; Galeazzi, Mauro; Iannone, Florenzo; et al.
ABSTRACT: Purpose : To identify factors associated with sustained response to interleukin (IL)-1 inhibition among demographic, clinical and therapeutic data in patients with Behçet disease (BD). Methods : BD patients treated with anakinra or canakinumab were enrolled. Patients were divided into two groups according to the clinical response: group 1 included subjects showing a treatment duration of at least 52 weeks and no secondary inefficacy during the first follow-up year; the remaining patients were included in the group 2. Demographic, clinical and therapeutic data were analyzed to identify significant differences between groups. Results : Eighteen patients were included in group 1 and 18 patients in group 2. A better response to IL-1 inhibitors was significantly more common among patients with BD-related uveitis ( p  = 0.006) and patients with a longer disease duration ( p  = 0.03). Conclusion : IL-1 blockade is effective in BD, especially in the subset of patients presenting eye involvement and in those with long-lasting disease.